2021
DOI: 10.3389/fpsyt.2021.693687
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Acceptance of a Smartphone-Based Virtual Agent Screening for Alcohol and Tobacco Problems and Associated Risk Factors During COVID-19 Pandemic in the General Population

Abstract: Background: During the current COVID-19 pandemic, alcohol, and tobacco are the most available substances for managing stress and can induce a risk of addiction. KANOPEE is a smartphone application available to the general population using an embodied conversational agent (ECA) to screen for experiences of problems with alcohol/tobacco use and to provide follow-up tools for brief intervention.Objectives: This study aimed to determine if the smartphone KANOPEE application could identify people at risk for alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Of these, papers were excluded (n = 38) if they were concerned with a different area of addiction (smoking, gambling, or technology), if their primary focus was not drug and alcohol addiction or SUD, or if they studied a different area of mental health. This saw 11 papers progress to full review, which yielded a further 3 studies through citation tracking [32][33][34][35][36][37][38]. The full-text of the accumulated 14 papers was considered.…”
Section: Papers Eligible For Inclusionmentioning
confidence: 99%
“…Of these, papers were excluded (n = 38) if they were concerned with a different area of addiction (smoking, gambling, or technology), if their primary focus was not drug and alcohol addiction or SUD, or if they studied a different area of mental health. This saw 11 papers progress to full review, which yielded a further 3 studies through citation tracking [32][33][34][35][36][37][38]. The full-text of the accumulated 14 papers was considered.…”
Section: Papers Eligible For Inclusionmentioning
confidence: 99%
“…Contrary to the previous ones, this modality is not invasive, costs less than traditional measurements, and benefits from its possibility of implementation in real conditions (e.g. with smartphone microphones) and could complete the information gathered by smartphone-based virtual agents, that are very well accepted by patients on a regular use [12,13].…”
Section: Sleepiness Detection Through Voicementioning
confidence: 99%
“…During this time, many households have faced isolation, fear, violence, drug abuse, and anxiety. The pandemic has affected not only physical health but also mental functioning ( 1 ). A recent study conducted among undergraduates in a Chinese college reported that 24.9% of the participants experienced psychological distress due to the COVID-19 pandemic ( 2 ).…”
Section: Introductionmentioning
confidence: 99%